Document Management System Based on Paperless - Wiwin Susanty; Taqwan Thamrin; Erlangga ERLANGGA; Ahmad Cucus (International Conference on Engineering and Technology Development (ICETD), 2012)
Loss documents and the high cost of document storage space are a major problem often faced by many organizations at this company, especially for those who have large amounts of paper documents. Therefore, we need a proper solution with the help of information technology known as the Document Management System. With this system, the paper documents are converted in digital form and stored in a disk or other digital storage facility (paperless).Furthermore to the search, discovery, display, printing, distribution and even documents can be done virtually through computer networks. Security policy can also be applied strictly in the management of these documents, so the only party entitled to can access the document according to its designation. Protection against the document is done digitally, so that relatively more secure and easier to use.Document Management System based on Paperless are effective and useful in an office to streamline in the process of documentation. The main benefit is that users can find needed information quickly, so it can help the process become faster, better, cheaper, and reduce environmental impacts (Green Computing). In this system of administration are routine operations performed by each individual in an organization or office activities.Technology and administration without paper is the efficiency in the use of paper, especially in terms of paperwork and correspondence in order to achieve certain objectives in managing the administrative management system or the idea of a paperless office. This paper present a paperless model for the university management system. A survey has been conducted that enlisted some fundamental characteristics required to implement successful paperless environment.